Hemorrhagic thoracic spinal epidural angiolipoma: a case report - Awang, Mohamed Saufi; Chan, Kin Hup; Zakaria@Mohamad, Zamzuri; Md Ralib @ Md Raghib, Ahmad Razali; Abd Rahman, Azlina (Faculty of Medicine, International Islamic University Malaysia, 2014)
Spinal epidural angiolipomas are rare benign tumors. The tumors contain both vascular and mature adipose components. Typically, they present with a progressive clinical course. Acute presentation is rare. We present a case of a fifteen-year-old girl who presented with a sudden onset of backpain followed by paraparesis with bladder and bowel incontinence. Neurological examination showed sensory loss below T10 with Grade 2 motor power. Spinal MRI showed long segment extradural lesion at T6-T9 level. Multiple laminectomy and excision of the tumor containing areas of hemorrhage was performed. Histopathology report revealed angiolipoma.